2023
DOI: 10.3389/fnins.2023.1249539
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbial transplantation limits neural injury severity and functional deficits in a pediatric piglet traumatic brain injury model

Madison M. Fagan,
Christina B. Welch,
Kelly M. Scheulin
et al.

Abstract: Pediatric traumatic brain injury (TBI) is a leading cause of death and disability in children. Due to bidirectional communication between the brain and gut microbial population, introduction of key gut bacteria may mitigate critical TBI-induced secondary injury cascades, thus lessening neural damage and improving functional outcomes. The objective of this study was to determine the efficacy of a daily fecal microbial transplant (FMT) to alleviate neural injury severity, prevent gut dysbiosis, and improve funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…Furthermore, the piglet brain shows a more similar progression of neural development, maturation, and myelination to human adolescents compared to rodent models; consequently, it allows for an age-dependent response to injury that is more appropriate for modeling pediatric TBI [ 36 , 37 ]. Our research team has recently demonstrated that the piglet TBI model shows gait deficits comparable to pediatric TBI patients, including loss of coordination and reduced motor control [ 11 , 38 , 39 , 40 ]. These key similarities in human and porcine neural and functional responses to TBI make the pig a valuable tool in assessing novel neuroimaging sensitivity to white matter integrity post-TBI.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the piglet brain shows a more similar progression of neural development, maturation, and myelination to human adolescents compared to rodent models; consequently, it allows for an age-dependent response to injury that is more appropriate for modeling pediatric TBI [ 36 , 37 ]. Our research team has recently demonstrated that the piglet TBI model shows gait deficits comparable to pediatric TBI patients, including loss of coordination and reduced motor control [ 11 , 38 , 39 , 40 ]. These key similarities in human and porcine neural and functional responses to TBI make the pig a valuable tool in assessing novel neuroimaging sensitivity to white matter integrity post-TBI.…”
Section: Introductionmentioning
confidence: 99%